Structure, microparameters and properties of crosslinked DGEBA/MTHPA: A molecular dynamics simulation - Xie, Qing; Liang, Shaodong; Liu, Bowen; Fu, Kexin; Zhan, Zhenyu; Lu, Lu; Yang, Xueming; Lü, Fangcheng; Huang, Zhengyong (AIP advances, 2018)
Investigating the relationship between microstructure and macroscopic properties of epoxy resin (EP) materials for high-voltage insulation at the molecular level can provide theoretical guidance for the synthetic design of EP. Here, using diglycidyl ether (DGEBA) as the resin matrix and methyl tetrahydrophthalic anhydride (MTHPA) as the curing agent, a set of crosslinked EP molecular models at different curing stages were constructed based on the proposed crosslinking method. We studied the influences of crosslinking density on micro-parameters and macro-properties employing molecular dynamics (MD) simulations. The results indicate that crosslinking of DGEBA/MTHPA is a contraction and exothermic process. The structural parameters and macroscopic properties are closely related to the degree of crosslinking. With the increase of crosslinking density, the mean square displacement (MSD) of the system decreases, and the segment motion in the models is weakened gradually, while, the fractional free volume (FFV) first decreases and then increases. In addition, the thermal and mechanical properties of DGEBA/MTHPA have a significant dependence on the crosslinking density. Increasing crosslinking density can improve the glass transition temperature (Tg), reduce the coefficient of thermal expansion (CTE), and enhances the static mechanical properties of DGEBA/MTHPA system. Furthermore, the relationship between microparameters and properties has been fully investigated. Free volume is an important factor that causes thermal expansion of DGEBA/MTHPA. Moreover, there is a negative correlation between MSD and mechanical moduli. By elevating temperature, the decline in mechanical moduli may be due to the exacerbated thermal motion of the molecules and the increasing MSD values.